Exploring the Intrinsic Limits of Nitrogenase Transfer from Bacteria to Eukaryotes - Soto, Gabriela Cynthia; Fox, Ana Romina; Ayub, Nicolás Daniel (Springer, 2019)
Biological nitrogen fixation is widespread among the Eubacteria and Archae domains but completely absent in eukaryotes. The lack of lateral transfer of nitrogen-fixation genes from prokaryotes to eukaryotes has been partially attributed to the physiological requirements necessary for the function of the nitrogenase complex. However, symbiotic bacterial nitrogenase activity is protected by the nodule, a plant structure whose organogenesis can be trigged in the absence of bacteria. To explore the intrinsic potentiality of this plant organ, we generated rhizobium-independent nodules in alfalfa by overexpressing the MsDMI3 kinase lacking the autoinhibitory domain. These transgenic nodules showed similar levels of leghemoglobin, free oxygen, ATP, and NADPH to those of efficient Sinorhizobium meliloti B399-infected nodules, suggesting that the rhizobium-independent nodules can provide an optimal microenvironment for nitrogenase activity. Finally, we discuss the intrinsic evolutionary constraints on transfer of nitrogen-fixation genes between bacteria and eukaryotes.